Exploring neuroinflammation as a potential avenue to improve the clinical efficacy of opioids. (November 2012) - Thomas, Jacob; Hutchinson, Mark R
Opioids are an extremely important part of medical practice, and for thousands of years, continued to provide relief from severe acute and chronic pain. Intriguingly, use of opioids activates endogenous counter-regulatory mechanisms resulting in increased sensitivity to noxious stimuli and the requirement for higher doses of opioids to reach an effective level of analgesia. Until recently, research into the counter regulators of opioid-induced analgesia had been focused on the role of neuronal receptors where the beneficial and detrimental actions of opioids were thought to be inseparable. It is now apparent from molecular and rodent data that opioids have non-neuronal, nonclassic, nonstereoselective sites of action. At these newly recognized sites, opioid activity significantly modifies the pharmacodynamics of opioids by eliciting proinflammatory reactivity from immunocompetent cells of the CNS. This review will examine the nonclassic actions of opioids specifically appreciating the actions of the released immune products.